Concepções de professores de Educação Física da Rede Pública na cidade de Bauru sobre altas habilidades/superdotação - Moraes, Rodolfo Lemes de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Students with giftedness presents specific issues in social behavior and their emotional characteristics, with spontaneous or high degree of interest and learning when compared to their peers of the same age. Their skills are noticed when the individual has a very large interest in a certain area of knowledge. Their highest level of production, creativity and originality in solving problems deserve to be highlighted. The manifestations of these gifted behaviors may be academic, creative-productive or a combination of both. The first is easily identified through the student's bulletin; the second requires opportunities for expression of student creativity. These behaviors are also related to Multiple Intelligences Theory, suggesting that these people could exhibit remarkable behaviors in one or more categories of intelligence. Through the Adapted Sport Pedagogy, the Physical Education in the school is able to provide opportunities for expression of creativity and develop the potentialities of Multiple Intelligences. Schoolwide Enrichment provides guidance and tools to develop person's abilities with gifted behaviors. Considering these factors, the objective was to identify knowledge (conceptualization, teaching action plans, pedagogical strategies, mapping of students, etc.) of the Physical Education teachers of public schools, elementary and middle schools, state network, about students with giftedness. Data collection was carried out through two questionnaires, which characterized the participants and verified their knowledge about the theme giftedness at Physical Education. An analysis of the association of factors by hierarchical clusters showed a strong association between satisfaction, performance, motivation and teachers' willingness to remain in the profession. It also showed that the search for information about AH / SD is due to the first contact with AH / SD students... (Complete abstract electronic acess below)

Alunos com Altas Habilidades/Superdotação (AH/SD) apresentam especificidades no comportamento social e suas características emocionais, com grau de interesse e aprendizagem espontâneos ou elevados quando comparados com seus pares de mesma idade. Suas habilidades são notadas quando o indivíduo tem um interesse muito grande em determinada área do conhecimento; o nível de produção é mais elevado, a criatividade e a originalidade na resolução de problemas merecem destaque. As manifestações dessas AH/SD, ou comportamentos de superdotação, podem ser acadêmicas, criativa-produtiva ou a combinação de ambas. A primeira é facilmente identificada através do boletim do aluno; a segunda requer oportunidades de expressão da criatividade do aluno. Esses comportamentos também estão relacionados às Inteligências Múltiplas, sugerindo que essas pessoas poderiam apresentar comportamentos notáveis em uma ou mais categorias da inteligência. Através da Pedagogia do Esporte Adaptado (PEA), a Educação Física (EF) escolar é capaz de proporcionar oportunidade de expressão da criatividade e desenvolver as potencialidades das Inteligências Múltiplas. O Enriquecimento Curricular proporciona orientações e ferramentas para desenvolver habilidades da pessoa com AH/SD. Considerando esses fatores, estabeleceu-se o objetivo de identificar os conhecimentos (conceituação; planos de ação docentes; estratégias pedagógicas; mapeamento de alunos, etc.) dos professores de Educação Física escolar (EFE) de escolas públicas, ensino fundamental e médio, da rede estadual paulista, sobre alunos com Altas Habilidades/Superdotação. A coleta de dados se deu por meio de dois questionários, que caracterizavam os participantes e averiguava seu conhecimento sobre o tema Altas Habilidades/Superdotação na EFE... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Superdotados; Enriquecimento curricular; Educação fisica; Inteligências múltiplas; Multiple intelligences